2010
DOI: 10.1111/j.1439-0507.2009.01763.x
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol and its antifungal activity against Candida species

Abstract: Resveratrol is a natural stilbene synthesised by plants. This compound has been shown to inhibit the growth of Candida albicans TIMM 1768 efficiently. Till date, no information is available for other Candida species. The evaluation of the antimicrobial activity of resveratrol was analysed by the inhibition of the growth and metabolism assays. Our data indicate that resveratrol is not effective against Candida albicans and non-C. albicans species (C. dubliniensis, C. glabrata, C. tropicalis, C. parapsilosis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 11 publications
1
26
0
2
Order By: Relevance
“…The effect of resveratrol (3,5,4-trihydroxystilbene), a close analogue of PTE, on C. albicans has been investigated previously (57)(58)(59). However, its antifungal effect was much weaker than PTE.…”
Section: Met14mentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of resveratrol (3,5,4-trihydroxystilbene), a close analogue of PTE, on C. albicans has been investigated previously (57)(58)(59). However, its antifungal effect was much weaker than PTE.…”
Section: Met14mentioning
confidence: 99%
“…However, its antifungal effect was much weaker than PTE. More specifically, Okamoto et al revealed that the MIC 50 of resveratrol against C. albicans SC5314 was about 200 g/ml, and resveratrol (Ն40 g/ml) could inhibit the yeast-to-hypha morphological transition of C. albicans (57), while Collado et al (58) and Weber et al (59) reported that resveratrol had no antifungal activity against C. albicans. In this study, we found that PTE has a much stronger antifungal effect against C. albicans than resveratrol, with a MIC 80 of 32 g/ml and a minimal concentration in- hibiting morphological transition of 4 g/ml.…”
Section: Met14mentioning
confidence: 99%
“…Among dietary polyphenols, resveratrol (3,4’,5-trihydroxy-trans-stilbene), found in the skin of grapes, blueberries, raspberries and mulberries [9], is known to be effective against bacterial and fungal infections [10, 11], cardiovascular diseases [12], metabolic diseases [13], and cancer [1416]. Resveratrol has also been reported to show anti-inflammatory effects [17], inhibit lipid peroxidation [18], and activate free radical scavenging [19], further supporting the evidence in the favor of the antioxidant activity of resveratrol.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the activity of resveratrol against C. albicans, there is still some controversy. Weber et al showed resveratrol did not show any significant effects on several Candida species [32]. However, the latest report suggested that resveratrol derivatives could affect on Candida species [13].…”
Section: Introductionmentioning
confidence: 97%